Advances in multimedia information processing – PCM 2017 : 18th Pacific-Rim Conference on Multimedia, Harbin, China, September 28-29, 2017, Revised Selected Papers.: 18th Pacific-Rim Conference on Multimedia, Harbin, China, September 28-29, 2017, Revised Selected Papers. Part I (2018) - Unknown
No abstract available